To the efficiency of locomotives of electric tractions on a hilly section of the railway - Ablyalimov O. (E3S Web of Conferences, 2023)
The results of the substantiation of the average kinematic parameters of the movement of freight trains and the energy efficiency indicators of the transportation work of locomotives of electric traction without stops and with stops on a virtual hilly section of the railway are presented. The stated goal of the research was realized through the theory of locomotive traction through a graphical method of integrating the differential equation of train motion, based on the finite increment method, with subsequent calculation of the numerical values of the specified parameters and indicators. Research results obtained in the form of tabular data, graphical dependencies and equations regression to determine the efficiency indicators of locomotives of electric traction on virtual and real hilly sections of railway, which are recommended on the practice work of specialists in the operation workshop of locomotive depots of the Uzbek railways.